Concept and Implementation of ESG Based on Balinese Local Wisdom: Tri Hita Karana - Sugiantari, Ida Ayu Putu Ayunda Aprilia; Keristina, Ni Made Deni (International Journal of Social Studies, 2026)
This research argues that the basic principles of ESG are not new and can be interpreted through local wisdom. Discussions about ESG are often dominated by Western-centric approaches that fail to integrate local wisdom. This research draws on the Balinese Tri Hita Karana (THK) philosophy, which harmonizes the relationship between humans, God, others, and nature. The purpose of this research is to explore ESG concepts and practices based on local wisdom in Indonesia. This research can provide a more comprehensive understanding in developing ESG strategies that positively impact society and the environment, while maintaining sustainable relationships between companies and local communities. THK provides a more holistic and context-based sustainability framework by incorporating spiritual and cultural dimensions. The implementation of THK has been proven to enhance local economic diversification, cultural preservation, and stakeholder education, establishing a holistic sustainability benchmark for local, national, and global adaptation. To achieve its objectives, this study reviewed 10 local wisdom-based ESG articles with an Indonesian background. To identify relevant articles, the study evaluated the Scopus, Web of Science, and Google Scholar databases. This research focused on the ESG concept and its implementation based on Tri Hita Karana. The analysis revealed that ESG planning, implementation, and evaluation that consider local wisdom can result in sustainable ESG practices. This research will also assist future researchers in conducting local wisdom-based ESG research through the identified research gaps. Additionally, this study recommends collaborative and adaptive strategies for the government, industry, and community to further mainstream THK as a universal principle for inclusive and resilient sustainable business.